Bank privatization in developing and developed countries: Cross-sectional evidence on the impact of economic and political factors - Boehmer, Ekkehart; Nash, Robert C.; Netter, Jeffry M. (Journal of Banking & Finance, 2005)
We examine how political, institutional, and economic factors are related to a country’s decision to privatize state-owned banks. Using a panel of 101 countries from 1982 to 2000, we find that political factors significantly affect the likelihood of bank privatization only in developing countries. Specifically, in non-OECD countries, bank privatization is more likely the more accountable the government is to its people. In contrast, none of our political variables affects the bank privatization decision in developed countries. Economic factors (such as the quality of the nation’s banking sector) are significant determinants of bank privatization in both OECD and non-OECD nations.